2021
DOI: 10.1038/s41598-021-95376-x
|View full text |Cite
|
Sign up to set email alerts
|

Performance and host association of spotted lanternfly (Lycorma delicatula) among common woody ornamentals

Abstract: Lycorma delicatula (spotted lanternfly) has a broad host range with a strong preference for the invasive host plant from its native range, tree of heaven (Ailanthus altissima); it had long been speculated that L. delicatula could not develop or reproduce without access to tree of heaven. In 2019, we found that this assumption was incorrect, but fitness was reduced in the absence of A. altissima in that the number of egg masses laid was dramatically fewer for insects reared on suitable non-A. altissima host pla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…None of these previous studies provided statistical data to guide the classification of new datasets for instar determination. Furthermore, studies of other insect species have shown that the size ranges for each instar can depend on factors such as date of emergence, diet (18), host plants, temperatures, and environment (e.g., laboratory vs fieldraised) (19) Indeed, prior research has indicated that SLF nymphs develop and survive differently when reared with different diets in the field (19,20), at different temperatures (21), and artificial conditions (i.e., enclosures or laboratory conditions) (1,16), but these studies did not consider how these factors affected instar morphometrics. In other insect and arthropod species, instar determination has often relied on Dyar's rule: the finding that nymphal body sizes tend to be distributed among distinct clusters because each instar stage attains a maximum body size before molting (22).…”
Section: )mentioning
confidence: 99%
“…None of these previous studies provided statistical data to guide the classification of new datasets for instar determination. Furthermore, studies of other insect species have shown that the size ranges for each instar can depend on factors such as date of emergence, diet (18), host plants, temperatures, and environment (e.g., laboratory vs fieldraised) (19) Indeed, prior research has indicated that SLF nymphs develop and survive differently when reared with different diets in the field (19,20), at different temperatures (21), and artificial conditions (i.e., enclosures or laboratory conditions) (1,16), but these studies did not consider how these factors affected instar morphometrics. In other insect and arthropod species, instar determination has often relied on Dyar's rule: the finding that nymphal body sizes tend to be distributed among distinct clusters because each instar stage attains a maximum body size before molting (22).…”
Section: )mentioning
confidence: 99%
“…Tree of heaven, Ailanthus altissima (Mill.) Swingle (Sapindales: Simaroubaceae), is often referred to as the primary or preferred host of L. delicatula, although it is not obligatory for completion of their development (7)(8)(9). Damage caused by L. delicatula phloem feeding has been reported on grapevine and peach trees in its invaded range in South Korea (4).…”
Section: Introductionmentioning
confidence: 99%
“…As L. delicatula is univoltine, establishing and maintaining a productive colony can be challenging. Information on such variables as diapause during the egg stage and nutritional needs for L. delicatula is still emerging (7)(8)(9)17). Here, we evaluated several sources of A. altissima plant material and abiotic conditions promoting L. delicatula development and survivorship and different substrates for the promotion of mating and oviposition under laboratory conditions to generate standardized methods for maintaining a colony of L. delicatula.…”
Section: Introductionmentioning
confidence: 99%
“…The spotted lanternfly, Lycorma delicatula (White), is a sap-feeding insect native to China. The main host plant of this species is the tree of heaven, Ailanthus altissima 1 , 2 , but it can utilise more than 70 plant species such as apples and grapes 3 5 . L. delicatula damages or even kills trees, including crops, by feeding on large amounts of plant sap and excreting honeydew on the leaf surfaces which promotes the growth of sooty mould fungus on them 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%